Eksplorasi konsep jiwa sehat dan jiwa sakit menurut pemikiran William James - Zahra, Ghefira Az (Maliki Interdisciplinary Journal, 2025)
William James was a philosopher and psychologist who made significant contributions to understanding religious experience and mental well-being. His concepts of the healthy and sick souls remain relevant in modern psychology, particularly in examining how spiritual experiences influence a person's psychological state. This article aims to analyze James's thoughts on these two concepts and their implications for the psychology of religion. Through a literary approach, this article finds that the sick soul often experiences an existential crisis that drives a deeper search for meaning, while the healthy soul tends to view life optimistically without much inner struggle. The results of the discussion indicate that James's perspective remains relevant in understanding the dynamics of spirituality and mental well-being and can serve as a basis for further research on the relationship between religion and psychology. This article also fills a research gap by presenting this study in Indonesian.